Perancangan Sistem Informasi Penjualan dan Pembelian Barang Berbasis Web Pada Mebel Balap Taufik - fuadil hasan; Kiky Zulkifli (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to design a web-based Sales and Purchase Information System at Mebel Balap Taufik to improve the effectiveness of transaction recording. Currently, the process of recording is still done manually using a note book, resulting in frequent recording errors, data duplication, late reports, and difficulties for business owners in monitoring cash flow in real-time. To overcome these problems, a web-based information system was developed using the PHP programming language, the CodeIgniter framework, and a MySQL database. The research method uses the SDLC Waterfall model approach, including observation, interviews, needs analysis, system design with UML, implementation, and testing using Blackbox Testing. Research data were collected through direct observation at Mebel Balap Taufik, interviews with business owners. The results of the study indicate that the designed system is able to automate the recording of sales transactions, purchases, stock management, and report preparation. The system helps owners minimize manual recording errors, speed up the reporting process, and improve operational efficiency. Testing using Blackbox Testing shows that all features run according to user needs.